Constative an analysis of slang words on Twitter / Nurul Syafika Zahidi and Norazean Sulaiman - Zahidi, Nurul Syafika; Sulaiman, Norazean (Universiti Teknologi MARA, 2023)
Due to the increasing numbers of online activities through social media platforms, the communication style also becomes more informal and open which resulted in slang being used too often among the users of social media. Therefore, this study focuses on whether English major students are also familiar with the use of slang in their communication through their tweets on Twitter. The research was conducted in accordance with Barseghyan's list of types of internet slangs, whereby the objectives of the research are to identify the types of slang used in Twitter, to investigate the functions of using slang words among students in Twitter, and to identify the meaning of slang words used by them in Twitter. This study is qualitative in nature which involved six participants. The data was obtained from tweets on Twitter that contained slang, and semi-structured interviews. The analysis found that these students implemented a variety of slang in their online communication such as shortening, punctuation and capitalizations, acronyms and abbreviations, clipping, compounding and repetition. The functions of slang used are pursuit of self-identity, emotive feeling and achieving politeness. In terms of the meaning, there are direct or indirect meanings depending on the context of the tweets. Thus, this study is likely to add to one's understanding of types of slang, the functions of using it and the meaning of the words.